The Profile of Psoriasis Vulgaris Patients: A Descriptive Study - Hidayati, Afif Nurul; Hendaria, Made Putri; Listiawan, M. Yulianto; Utomo, Budi; Damayanti, Damayanti; Prakoeswa, Cita Rosita Sigit; Anggraeni, Sylvia; Umborowati, Menul Ayu; Citrashanty, Irmadita; Ervianti, Evy (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Psoriasis is a skin disease that occurs due to proliferation and differentiation disturbances of the epidermis. This chronic condition often reduces the human quality of life. There have been studies investigating psoriatic patient profiles and treatments, but few are conducted in Surabaya. Hence, those studies cannot fully represent the population demographic in Surabaya. Purpose: To investigate the prevalence of psoriasis vulgaris and the sociodemographic profile of the patients in Dr Soetomo General Academic Hospital. Methods: This was a Retrospective study psoriasis vulgaris patients in January 2016–December 2018. The data were collected by retrieving Electronic Medical Records (EMR) as secondary data. Result: The psoriasis vulgaris prevalence of outpatients was 0.46% and 4.59% in inpatients. Most study subjects were adults aged 18 and above (98.1%), most of the patients were obese (46.3%), the most common provoking factor was focal tooth infection (33.8%) and stress (28.8%), and none reported family history of psoriasis. Conclusion: Some results are similar to other studies conducted in Surabaya, which were the obesity and Type 2 Diabetes Mellitus (DM) being strong a factor to psoriasis development. However, the result on psoriasis family history was not in line with other studies.